AB0280 The comparative responsiveness of the patient self-report questionnaires and composite disease for assessing rheumatoid arthritis activity in routine care. (23rd January 2014) - Salaffi, F.; Ciapetti, A.; Gasparini, S.; Carotti, M.; Gutierrez, M.; Bombardieri, S.
Abstract : Objectives: To evaluate the internal and external responsiveness of the patient self-report questionnaires, comparatively to the traditional composite indices for assessing the activity of rheumatoid arthritis (RA) in everyday practice. Methods: One hundred and ninety-one RA out-patients completed the CLinical ARthritis Activity (PRO-CLARA), the Rheumatoid Arthritis Disease Activity Index (RADAI), the Routine Assessment of Patient Index Data (RAPID3), and the Patient Activity Score (PAS). Simultaneously, the Disease Activity Score - 28 joints based on CRP (DAS28-CRP) and ESR (DAS28-ESR), the Simplified Disease Activity Index (SDAI), the Clinical Disease Activity Index (CDAI), and the Mean Overall Index for RA (MOI-RA) were computed in each patients. Sensitivity to change was assessed in after 6 months of treatment with disease-modifying antirheumatic drugs or biologics. Internal responsiveness was evaluated with the effect size (ES) and standardized response mean (SRM). External responsiveness was investigated by receiver operating characteristic (ROC), in categories of respondents, stratified according to the response on an item on change in overall health. In addition, change scores were compared by calculating correlation coefficients. Results: Significant differences in internal and external responsiveness were not found between self-report questionnaires and composite indices. The internal responsiveness of the self-report questionnaires and composite measures was large, with SRM and ES ranging from 1.03 (RADAI) to 1.80 (DAS28-ESR) and higher than that of the each individual measures. The responsiveness of the PRO-CLARA was equal to the DAS28-ESR, DAS28-CRP, SDAI or MOI-RA, but better than the CDAI. The RADAI and PAS were less responsive than the PRO-CLARA and RAPID3. The area under ROC curve of the PRO-CLARA gives identical results to those provided by other comparator composite indices. The score changes of all combinations were highly correlated (p<0.0001). Conclusions: The self-report questionnaires showed comparable internal and external responsiveness that the composite activity scores and allow the detection of rheumatoid disease activity. They appear suitable for clinical decision making, epidemiologic research, and clinical trials. Further longitudinal studies are needed to validate these encouraging results. Disclosure of Interest: F. Salaffi Grant/Research support from: FS has attended advisory board meetings for Bristol-Myers Squibb, Abbott Immunology, Wyeth Lederle and Pfizer and has received research support from Bristol-Myers Squibb. A. Ciapetti: None Declared, S. Gasparini: None Declared, M. Carotti: None Declared, M. Gutierrez: None Declared, S. Bombardieri: None Declared